PENGARUH IRADIASI GAMMA TERHADAP DEGRADASI ZAT WARNA DIRECT ORANGE 34 DALAM AIR - Sugita, Purwantiningsih; Winarno, Ermin Katrin; Anriani, Lia (Jurnal Teknologi Lingkungan, 2000)
The aim of this experiment is study on technique of gamma irradiaton in analyzing dying agent direct orange 34 in waste water. Direct orange 34 was dispersed to oxalic and malic acids when the 60Co irradiated. The result showed that dose and dose rate of 60Co were less than 10 kGy and 7.57 kGy/hour, respectively. While, the pH of the first solution was 7.0. The technique showed that the chemical oxygen demand of dye solution was decreased from 60.38 to 4.90 ppm.